2016
DOI: 10.1038/srep32482
|View full text |Cite
|
Sign up to set email alerts
|

Location and Visualization of Working p-n and/or n-p Junctions by XPS

Abstract: X-ray photoelectron spectroscopy (XPS) is used to follow some of the electrical properties of a segmented silicon photodetector, fabricated in a p-n-p configuration, during operation under various biasing configurations. Mapping of the binding energy position of Si2p reveals the shift in the position of the junctions with respect to the polarity of the DC bias applied. Use of squared and triangular shaped wave excitations, while recording XPS data, allows tapping different electrical properties of the device u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
3
1
Order By: Relevance
“…Even though we have not been able to strongly correlate the observed extra peak to any of the previously reported XPS emission data, some authors have demonstrated that similar changes in Si/SiO2 interface band-bending can be probed by XPS measurements of the Si 2p peak shifting [7], [9]- [11]. In our case we do observe a slight shift from the Si 2p peak upon GO deposition, but it is rather a strong peak splitting what we believe to exhibit the differential charging at the interface.…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…Even though we have not been able to strongly correlate the observed extra peak to any of the previously reported XPS emission data, some authors have demonstrated that similar changes in Si/SiO2 interface band-bending can be probed by XPS measurements of the Si 2p peak shifting [7], [9]- [11]. In our case we do observe a slight shift from the Si 2p peak upon GO deposition, but it is rather a strong peak splitting what we believe to exhibit the differential charging at the interface.…”
Section: Resultscontrasting
confidence: 52%
“…If our assignment is correct it may be possible then to correlate the depth of the depleted region to the surface/bulk doublet ratio and perhaps aid the current limitation of the proposed method in Ref. [11].…”
Section: Resultsmentioning
confidence: 99%
“…As described elsewhere, such setup conguration can be used for pseudo-operando characterizations. 41,42 The BAEE data are potential corrected for being compared with the data collected during the interface experiments (see Fig. S5 †).…”
Section: Interface and Bias Assisted Electron Exposure Experimentsmentioning
confidence: 99%
“…Based on X-ray photoelectron spectroscopy (XPS), it is often possible to resolve in a noncontact manner the electrostatic potential at selected domains. As previously demonstrated by chemically resolved electrical measurements (CREM), the electron analyzer acts then as a chemically selective voltmeter, [12][13][14][15] allowing for the subtleties of charge trapping and internal fields in heterojunctions to be identified. 16 Here, we exploit recent instrumental developments in our CREM setup for the study of ZnOS.…”
mentioning
confidence: 99%